Cultural difference in maladaptive functions of perfectionistic self‐presentation. Issue 3 (20th May 2019) - Wang, Yiheng; Li, Liman Man Wai; Xie, Fuzhe
Abstract : Perfectionistic self‐presentation (PSP), which describes an expressive aspect of perfectionism in the interpersonal domain, is a defensive form of perfectionism that has been relatively understudied. Although existing evidence obtained from Western societies has consistently shown maladaptive functions of PSP, the question of whether these patterns are universal remains unanswered. The current research explored the potential moderating effect of culture by evaluating whether the negative influence of PSP is weaker in Asian societies that encourage the use of defensive interpersonal strategies than in Western societies. Two studies recruiting Chinese and North American participants were conducted. In Study 1 ( n  =   302), the results showed that the relation between PSP and personal mastery was positive among Chinese participants and was negative among North American participants. In contrast, a positive relation between PSP and perceived constraints was observed in both cultures. Study 2 ( n  =   295) replicated the findings obtained in Study 1. In addition, the findings showed that the relation between PSP and self‐esteem, but not that between PSP and depression, was moderated by participants' cultural backgrounds. Taken together, these results indicate both universal and culturally specific patterns regarding the influence of PSP, suggesting that PSP is a complex construct.